2019
DOI: 10.3389/fpubh.2019.00009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Assessment of Economic Burden of Disease in Relation to Out of Pocket Expenditure

Abstract: Background: The economic costs associated with morbidity pose a great financial risk on the population. Household's over-dependence on out-of-pocket (OOP) health expenditure and their inability to cope up with the economic costs associated with illness often push them into poverty. The current paper aims to measure the economic burden and resultant impoverishment associated with OOP health expenditure for a diverse set of ailments in India.Methods: Cross-sectional data from National Sample Survey Organization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Social isolation is an additional stressor to an already highly stressful world environment and people's extensive fear of the novel COVID-19 pandemic threat (Bavel et al, 2020;LeDoux, 2012;Mobbs et al, 2015). In addition, social distancing included full lockdowns in many countries, as well as in Israel, with dramatic economic effects (Anser et al, 2020;Sangar et al, 2019). Adverse local and global economic impacts, in addition to drastic personal income reduction, may be detrimental to people's psychological health and general well-being (Xiao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Social isolation is an additional stressor to an already highly stressful world environment and people's extensive fear of the novel COVID-19 pandemic threat (Bavel et al, 2020;LeDoux, 2012;Mobbs et al, 2015). In addition, social distancing included full lockdowns in many countries, as well as in Israel, with dramatic economic effects (Anser et al, 2020;Sangar et al, 2019). Adverse local and global economic impacts, in addition to drastic personal income reduction, may be detrimental to people's psychological health and general well-being (Xiao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, meta-analysis to determine the effect of various factors associated with CHE could not be conducted. Sangar et al, (2019) found that headcount for CHE was more among richer sections as compared to the poorer ones. Chauhan et al, (2018) found that the odds of CHE were higher for lower income quartile patients (OR: 5.6, 95% CI: 2.6-12.4, p-value: <0.001) than those in the highest income quartile.…”
Section: Correlates Of Catastrophic Health Expenditure On Cancer Carementioning
confidence: 91%
“…2 Shortcomings and Inefficiencies of Today's Healthcare System. 21 , 22 ARR, absolute risk reduction; RRR, relative risk reduction; RCT, randomized controlled trial …”
Section: Navigating the Complexities In Heart Failure Patients To Meet The Value Imperativementioning
confidence: 99%